2021
DOI: 10.3390/en14030691
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Emissions in SI Engines Fueled with LPG

Abstract: Ammonia is a toxic exhaust component emitted from internal combustion engines. Both pure ammonia and the products of its reaction with nitrogen and sulfur compounds, being the source of particulate matter (PM) emissions, are dangerous for human health and life. The aim of the article was to demonstrate that NH3 can be produced in exhaust gas after-treatment systems of spark-ignition (SI) engines used in light-duty vehicles. In some cases, NH3 occurs in high enough concentrations that can be harmful and dangero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The mechanisms that take place under these conditions are the water-gas (CO) shift reaction, producing H 2 and the reaction of NO and H 2 [58]. The availability of H 2 and CO, the exhaust gas temperature, and the lambda also affects small differences in the slopes of the cumulative NH 3 functions between different temperatures [59].…”
Section: Cold Startmentioning
confidence: 99%
“…The mechanisms that take place under these conditions are the water-gas (CO) shift reaction, producing H 2 and the reaction of NO and H 2 [58]. The availability of H 2 and CO, the exhaust gas temperature, and the lambda also affects small differences in the slopes of the cumulative NH 3 functions between different temperatures [59].…”
Section: Cold Startmentioning
confidence: 99%
“…is actually due to wide application of the traditional and advanced technology with possible hydrogen saturation during long term service and engines hydrogen cleaning effect . From the investigation of the operation principle of internal combustion engines [1,[3][4][5]9,[35][36][37], it follows that the mechanical movement of its elements is largely determined by the kinematics of the crank mechanism, fluid hydrodynamics in the channels, as well as more complex forms of movement: chemical and thermal movement, that is the processes of releasing and transferring the heat to the working fluid in the engine cylinder. Thermodynamic and heat transfer are important systems in the engine [6][7][8][9][10]13,18,21].…”
Section: Literature Surveymentioning
confidence: 99%
“…The classification of nanofluids and the analysis of theoretical advances to modeling the transfer coefficients are given in [19]. In particular, it is noted that a rigorous theory of transfer processes in nanofluids has not yet been developed, and the application of thermal conductivity modeling by molecular dynamics methods still gives predictions different from the classical theory [33][34][35][36][37][38][39][40][41]. However, none of the works mention how to avoid sediment on the bottom of the engine cooling channel of "light" nanoparticles under the action of inertial and gravitational forces.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Paper [23] presents the results of ammonia emission tests from a spark-ignition engine powered by LPG in connection with the use of the TWC reactor in the exhaust gas cleaning system. The study showed that in the case of high temperature of the catalytic reactor and periodic enrichment of the mixture, the emission of ammonia may be increased.…”
Section: Fuel Installations For Unconventional Fuels In Ic Enginesmentioning
confidence: 99%